The role of the nurse in improving the quality of healthcare - Magdalena Anna Wasik (Kazimierz Wielki University, 2020)
Introduction The nurse provides medical care for the patient, including nursing, administering medicines and performing injections. She assists the doctor in the process of diagnosis and treatment. The definition of this profession changes as a result of the development of science and increasing expectations of health care. The development of this profession is evidenced by developed models of nursing, which will focus on the practical application of the acquired knowledge. Aim The aim of this work was to present the tasks and competences of nursing and the role of this profession in improving the quality of patient care. Material and method The paper uses the method of literature analysis. The material used in the paper comes from publications published in a compact form and scientific articles. Results The review of the collected scientific material showed that nurses have a significant impact on the quality of health care and the functioning of the entire facility. Healthcare institutions belong to organizations in which the quality of services translates into the patient's health and life. Care should therefore be a priority for the entire staff, especially for the nurses who first meet the patient and spend a lot of time with him. Patients expect medical knowledge from nurses first and foremost, but also safety, trust and proper communication. Conclusions In recent years, nursing has been constantly changing, which means that people in this profession have to take various actions for their development. Patient expectations are also changing. Their opinion and satisfaction is important for success. A satisfied patient will surely use the services of the facility again.